2017
DOI: 10.1111/cei.13046
|View full text |Cite
|
Sign up to set email alerts
|

Selective HDAC6 inhibition decreases early stage of lupus nephritis by down-regulating both innate and adaptive immune responses

Abstract: SUMMARYWe have demonstrated previously that histone deacetylase (HDAC6) expression is increased in animal models of systemic lupus erythematosus (SLE) and that inhibition of HDAC6 decreased disease. In our current studies, we tested if an orally active selective HDAC6 inhibitor would decrease disease pathogenesis in a lupus mouse model with established early disease. Additionally, we sought to delineate the cellular and molecular mechanism(s) of action of a selective HDAC6 inhibitor in SLE. We treated 20-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In addition, our recent data have shown that treatment of human SLE-derived PBMCs with the HDACi vorinostat results in hyperacetylation of histone H4, chromatin decondensation, restoration of the DNA repair capacity, and decreased apoptosis rates [4]. These results are in line with previous data, showing that HDACi ameliorate disease in lupus mouse models [151][152][153]. Also, treatment of lupus-prone Mrl/lpr mice with the HDACi panobinostat significantly reduced circulating naïve B and plasma cell numbers and the levels of autoantibodies [154].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our recent data have shown that treatment of human SLE-derived PBMCs with the HDACi vorinostat results in hyperacetylation of histone H4, chromatin decondensation, restoration of the DNA repair capacity, and decreased apoptosis rates [4]. These results are in line with previous data, showing that HDACi ameliorate disease in lupus mouse models [151][152][153]. Also, treatment of lupus-prone Mrl/lpr mice with the HDACi panobinostat significantly reduced circulating naïve B and plasma cell numbers and the levels of autoantibodies [154].…”
Section: Discussionsupporting
confidence: 88%
“…While nuclear HDAC is critical for epigenetic regulation, which ultimately determines cell differentiation and function, cytosolic HDACs are involved in posttranslational modification of non-histone proteins in the cytosol, which are essential for cellular functions such as intra-cellular transport and cell migration among others [7]. HDAC activity in RA patients is higher than that in healthy controls, and HDAC inhibitors are effective in murine models of RA [8][9][10][11][12]. Non-specific pan-HDAC inhibitors, which suppress multiple isoforms of HDAC with pleiotropic effects, have anti-inflammatory properties; however, they are also associated with side effects such as fatigue, diarrhea, nausea, and neutropenia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…While nuclear HDAC is critical for epigenetic regulation, which ultimately determines cell differentiation and function, cytosolic HDACs are involved in post-translational modification of non-histone proteins in the cytosol, which are essential for cellular functions such as intra-cellular transport and cell migration among others [7]. HDAC activity in RA patients is higher than that in healthy controls, and HDAC inhibitors are effective in murine models of RA [8][9][10][11][12]. Non-specific pan-HDAC inhibitors, which suppress multiple isoforms of HDAC with pleiotropic effects, have anti-inflammatory properties; however, they are also associated with side effects such as fatigue, diarrhea, nausea, and neutropenia [13,14].…”
Section: Introductionmentioning
confidence: 99%